Food grain losses associated with indigenous storage methods and development of storage facilities for food security - Chattha, Shakeel Hussain; Che Man, Hasfalina; Mirani, Benish Nawaz; Mahadi, Muhammad Razif; Lee, Teang Shui (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
The deterioration of wheat grains in terms of various quality parameters was observed during storage in traditional and designed structures for 12 months. As a result of the laboratory analysis and statistical data evaluation, protein (11.78%), lipid (2.4%), ash (1.76%) and starch (64.87%) were found maximum in grain samples taken from straw-clay bin followed by concrete block bin, ferrocement bin, earthen bin, bulk covered and room type store after 12 months of storage. The highest moisture (15.12%), insect-damage (26%), fungi (25%) and aflatoxin (13.3 μg kg-1) was observed in grains stored in room store followed by bulk covered, earthen bin, ferrocement bin, concrete bin and straw-clay bin.